Dukungan Keluarga dalam Keikutsertaan KB pada Pasangan Usia Subur di Desa Argomulyo Sedayu Bantul Yogyakarta - Dwi Puspitasari; Siti Nurunniyah (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2014)
Family planning (FP) participation in 6 village located in Argomulyo, Sedayu, namely Puluhan, Kemusuk Kidul, Karanglo, Pedes, Surobayan and Kaliberot was 59.22%. The percentage was lower than the average number of Bantul which reached 81.40%. The progress of family planning programs can not be separated from their families since the family support is closely related to encouragement or motivation given to the reproductive age couples to participate in FP. The purpose of this study was to determine the relationship between family support and the participation of FP of reproductive age couples Argomulyo village Sedayu, Bantul, Yogyakarta. Study design used in this study was cross sectional. The total population of reproductive age couples in Argomulyo village were 916 respondents. The sampling technique was done by total sampling. The research instrument used in the form of questionnaires. Hypothesis testing with chi-square test (α=0.05). From the data analysis between family support and FP participation variables resulted on OR=19.09 (95%CI:12.614-28.875) and contingency coefficient = 0.479 and the FP participation. In conclusion, there was a positive relationship between family support with the FP participation on the spous of reproductive age couples in Argomulyo village, Sedayu, Bantul, Yogyakarta.